2011
DOI: 10.1111/j.1601-0825.2011.01837.x
|View full text |Cite
|
Sign up to set email alerts
|

Are oral and dental diseases linked to cancer?

Abstract: Oral infections may trigger malignant transformation in tissues of the mouth and other organs. However, scientific evidence to date remains weak and further well-conducted studies are warranted before cancer can be properly added to the list of oral infection-related systemic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 61 publications
2
28
0
2
Order By: Relevance
“…The recent literature also reports associations between the salivary microbiota and non-oral disease. Specific microbial consortia have been associated with obesity [9], [10], cancer [11], [12], HIV [13], inflammatory bowel disease [14], and atherosclerosis [15]. The possible value of the salivary microbiota for the early diagnosis of disease has also been noted [2].…”
Section: Introductionmentioning
confidence: 99%
“…The recent literature also reports associations between the salivary microbiota and non-oral disease. Specific microbial consortia have been associated with obesity [9], [10], cancer [11], [12], HIV [13], inflammatory bowel disease [14], and atherosclerosis [15]. The possible value of the salivary microbiota for the early diagnosis of disease has also been noted [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, two studies from China found an association between tooth loss and gastric cancer [3,4]. Putative mechanisms involved in the association between tooth loss and orodigestive cancers have been reviewed by Meurman and Bascones-Martinez [7], and infection and inflammation have been proposed as important risk factors. Orodigestive cancers were defined as cancers in the oral cavity and pharynx, esophagus, stomach, pancreas, liver, and colon, rectum or anus, as described in a recent report [8].…”
Section: Introductionmentioning
confidence: 99%
“…10 The putative mechanisms involved in the association have been further reviewed by Meurman and Bascones-Martinez. 11 Considering these observations, the hypothesis of the present study was that dental plaque is associated with premature death in cancer. A high amount of dental plaque indicates poor oral hygiene and, subsequently, was thought to be a surrogate for increased risk for dental infections.…”
Section: Introductionmentioning
confidence: 88%